Kết quả nghiên cứu mới về ranh giới Devon-Carbon tại nam Cát Bà, Hải Phòng bằng phương pháp MSEC - Thoa, Nguyễn Thị Kim; Ellwood, Brooks B.; Phương, Tạ Hòa; Lan, Lưu Thị Phương; Trưởng, Đoàn Nhật (Vietnam Journal of Earth Sciences, 2005)
We have been using magnetic susceptibility (MS) measurements of Paleozoic marine rocks, in conjunction with biostratigraphic control, for highresolution chronocorrelation and have named the method Magnetosusceptibility Event and Cyclostratigraphy(MSEC). MSEC is a composite of the MS record of marine strata and the coeval biostratigraphic record , and MSEC chronozones have boundaries which are isoch ronous. MS in marine sediments is a measure of the abudance of paramagnetic and ferimagnetic grains resalting from detrial input of lithogenic material into the marine system, due primarily to erosion driven by eustasy and climate. In those sections we have examined, MSEC trends of increasing MS magnitude correlate well with faling sea-level (regression), while trends of decreasing MS magnitude correlate whith nsmg sea-level (transgression). The use of MS data in the development of MSEC as a method for highresolution correlation of sedimentary strata has been decribed by Cricket al. (1997) and Ellwood et al. (1999; 2000). When we renalysed the MSEC results obtained in 2002 [1 OJ we found 3 MSEC tendency of variations between layers 20-21, 33a -34 and 36-38. To choice one of them to be the MSEC character of boundary D-C have to be based only on the paleontological control for correlation. According to the new paleontological finding [9] the D-C boundary may be situated between layers 37-38, but these layers are situated on the top of site, so, we can not follow the tendency of MSEC on the site. In 2003 the new road had cut the D-C site in Nam Cat Ba and the exposure of site allowed to sampling continuously for the MSEC method from layers 100 to 144. Here we present new results from Devonian-Carboniferous boundary sections in Cat Ba based on the new investigation results of paleontology and MSEC at the same site. New MSEC results confirm the location of D-C boundary in Nam Cat Ba between layers 118-122. The new paleontological research of Ta Hoa Phuong et all., 2005 ( in press) also proposed the same results.